Arterial thrombosis in unusual sites: A practical review. (15th October 2018) - O'Donnell, Matthew; Shatzel, Joseph J.; Olson, Sven R.; Daughety, Molly M.; Nguyen, Khanh P.; Hum, Justine; DeLoughery, Thomas G.
Abstract: While cardiovascular disease is common, occasionally hematologists and other practitioners will encounter patients with arterial thrombosis/infarction in unusual sites, without clear cause or obvious diagnostic and treatment paradigms. Contrary to the more commonly encountered cerebrovascular accident and cardiovascular disorders, the various infarctions outlined in this review have unique presentations, pathophysiology, workup, and treatments that all hematologists should be aware of. This review outlines the current literature on arterial thrombosis, with consideration given to anatomic sources and hypercoagulable associations, while focusing on the epidemiology, pathophysiology, provoking factors, and current recommended treatments for intracardiac thrombus, primary aortic mural thrombus, visceral infarctions, and cryptogenic limb ischemia to provide a useful and practical review for the practitioner.